2013
DOI: 10.1038/icb.2013.68
|View full text |Cite
|
Sign up to set email alerts
|

Follicular helper T‐cell memory: establishing new frontiers during antibody response

Abstract: The generation of immunological memory during an immune response is a hallmark of the adaptive immune system. Follicular helper T (Tfh) cells are a CD4 þ T-cell subset specialised to regulate antibody response. Emerging evidence suggests that during antibody response, Tfh memory is generated along with the generation of B-cell memory. There are multiple layers for the differentiation and function of memory Tfh cells. Both early committed precursor Tfh cells and effector Tfh cells exiting germinal centres can c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 75 publications
1
47
1
Order By: Relevance
“…Indeed, recent studies reported that CTLA-4 controls B cell responses by intrinsic and extrinsic mechanisms (36)(37)(38), in particular at the T follicular helper cell level, a specialized subset of memory lymphocytes (39)(40)(41). Although SRBC challenge is considered as a Tdependent primary humoral response model in rodents, baboons (but also other Old World primates, apes, and humans) are naturally immunized against anti-Gal carbohydrate residues (26) expressed by microorganisms and also other mammals (e.g., sheep).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent studies reported that CTLA-4 controls B cell responses by intrinsic and extrinsic mechanisms (36)(37)(38), in particular at the T follicular helper cell level, a specialized subset of memory lymphocytes (39)(40)(41). Although SRBC challenge is considered as a Tdependent primary humoral response model in rodents, baboons (but also other Old World primates, apes, and humans) are naturally immunized against anti-Gal carbohydrate residues (26) expressed by microorganisms and also other mammals (e.g., sheep).…”
Section: Discussionmentioning
confidence: 99%
“…These cells have been termed as peripheral T follicular helper cells (pTfh cells), as they share functional properties with GC-Tfh cells and are capable of providing help to B cells to produce antibodies by promoting somatic hypermutation and class-switch recombination (22)(23)(24)(25). The true relationship between pTfh and lymphoid Tfh cells has not yet been established, but experimental studies with mice (26) suggest that circulating pre-Tfh cells enter lymphoid follicles and traffic to GCs as mature Tfh cells; recent data imply that GC-Tfh cells exit the LN as memory cells (27). We hypothesized that pTfh cells are a key subset of circulating memory CD4 T cells and could constitute an important HIV reservoir.…”
Section: Al Have Identified Central Memory (T CM ) and Transitional mentioning
confidence: 99%
“…As the measurement of human GC Tfh cell from lymphoid follicles could hardly be performed, the investigation of circulating Tfh-like cells are widely accepted. In recent years a number of observations have indicated that circulating Tfh cells represent a partial differentiated state; however, they express Tfh-related markers at lower intensity and maintain functional characteristics to promote B cell differentiation [32,33]. At the periphery, Tfh-like cells may represent a memory CD4…”
Section: Cd27mentioning
confidence: 99%